The Influence of Service Quality on Customer Satisfaction: Evidence from Public Sector and Private Sector Banks in Kurdistan/Iraq: The Influence of Service Quality on Customer Satisfaction - Othman, Bestoon Abdulmaged (International Journal of Advanced Science and Technology, 2020)
The purpose of this research study is to determine the satisfaction level of banking clients with respect to the quality of the various services supplied by their bank and their satisfaction with the bank. The service quality is researched in a variety of aspects. There is also an attempt to find out which dimension of service quality can improve customer satisfaction. Respondents are selected using stratified random sampling from a range of different demographic features. Banks are chosen for sampling from both the government and private sectors. Using a convenience sampling technique, the required data were gathered from 384 participants using a structured questionnaire. Findings show that the service quality and all its’ dimensions are associated with customer satisfaction significantly and positively. The banking sector is an important industry in the economy of Kurdistan and in the last century has seen unprecedented development and raging competition. Therefore, this study was specifically carried out to explore this phenomenon and to seek empirical justification in this regard by considering the quality of service as the main contributing factor to the satisfaction of customers. Keywords: Public Sector and Private Sector Banks, customer satisfaction, service quality, Kurdistan